Modification of Recycled HDPE Composite with OPEFB Microfibers Through the Melt Blend Extruder Process - Zulnazri Zulnazri; Rozanna Dewi; Novi Sylvia (Jurnal IPTEK, 2020)
Oil palm empty fruit bunches (OPEFB), have not many been used as a have economic value material. OPEFB fiber content can be using as a filler to composites fabrication. The fiber contained in the OPEFB can be increase composites quality because have high thermal and mechanical properties. SEM analysis shows that OPEFB waste with a size of 63 and 90 ?m is suitable to be use as a filler because of the compatibility of the fiber and matrix matrix. As with the results of the DSC analysis, the melting point of HDPE-TKKS composite with 63 ?m fiber size reaches 133.58 0C while the melting point of HDPE-TKKS composite with 90 ?m fiber size reaches 134.41 0C. The FTIR test results also show that the indications of the two samples have the same chemical composition, namely lignicellulose. The best tensile strength is obtained which is equal to 21.11 MPa and the force required to break the composite is 391.56 N, these results were obtained from composites with a ratio of 60: 40 (matrix : filler) and 90 µm fiber size.Key words: Plastic, HDPE, fiber, OPEFB, composite